Lessons Learned From Trauma Injuries in Arbaeen 2019 in Ilam Province, Iran - Mozafari, Aliashraf; Shafiei, Elham; Jamshibeigi, Yousef; Sahebi, Ali (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Arbaeen is the largest peaceful religious gatherings on Earth. In this event, millions of people go to the holy city of Karbala in Iraq.  Annually, about 20 million pilgrims attend Arbaeen ceremony, including about three million foreigners, that most of whom are Iranians. Ilam province is located near Iran’s western border with Iraq. Every year, many Iranian pilgrims enter Iraq through Ilam borders for the Arbaeen ceremony, which lasts two weeks before and after Arbaeen day. Pilgrims after the religious rituals enter to their home.